Kepemimpinan di Atas Kapal - Rini Setiawati; Aswanti Setyawati; Honny Fiva Akira (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2018)
The leadership of a ship captain is often a philosophy or role model that is ideally used for professional leaders and family leaders. As we often hear, a leader is commonly related to a boat captain who leads a fleet across a vast sea to the dock, with the power to control the steering wheel. The purpose of this study is to explore the character of the captain's leadership on a ship that can be taken as a leadership philosophy in general. The research method used was a phenomenological approach since the problems studied involve problems that developed in the life of the captain. The phenomenology approach is one of the qualitative method approaches. Broadly speaking, leadership on board represents the ability to gain respect and authority from the crew. On the ship, leadership is a requirement for the growth of the organization of crew activities. In the shipping industry, there is a constant need to identify and nurture future leaders who have the potential to excel in critical leadership roles on board.